ANALYZING THE POSITIVE & NEGATIVE POLITENESS STRATEGIES PERFORMED IN ELT CLASSROOM INTERACTION - Dedi Aprianto (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
The practices of pragmatic politeness strategies in ELT contexts have been considered as the today’s important issues in ELT, what so-called as language in use in classroom discourse. Classroom interaction is the integral part of Classroom Discourse Analysis. This study aimed at finding what politness strategies employed by the classroom participants (lecturers students) and the  frequency of the politeness usages. This study was carried out by using a descriptive-qualitative research method. The data were obtained from the conversation done by all participants of ELT classroom; lecturers-learners, learners-lecturers, and learners-learners at the sixth semester of English Education department of Mandalika University of Education (the former IKIP Mataram). The data of research were analyzed through the process of identifying, classifying, grouping and making conclusion, then discussing. Of the two politeness strategies which are found are seven positive politeness consists of  strategy 1, strategy 2, strategy 3, strategy 4, strategy 5, strategy8 (claim common grounds) and strategy 13 (convey that S and H are cooperators). The negative politeness are strategy 1 (be indirect), strategy 2 (don’t presume/assume), strategy 4, strategy 5 (don’t coerce H), strategy 6, strategy 7, and strategy 9 (communicate S’s want to not impinge on H). The most-frequently employed politeness strategies are positive politeness strategies within various (sub) strategies under ELT classroom contexts. The more usages of positive politeness suggest the situation of classroom must have been little bit egalitarian atmosphere amongs all the participants; lecturers-students in doing ELT process. Those feel cofortable, clossed, friendly, and inclusive to the addresse in ELT contexts.